A Recent Late Sasanian Discovery North of the Persian Gulf. A Report on the First Season of Excavations at Tomb-e Pargan in Hormozgan, Iran - Asadi, Ahmadali; Kouhpar, Seyed Mehdi Mousavi; Neyestani, Javad; Nobari, Alireza Hojabri (Anabasis. Studia Classica et Orientalia, 2014)
The results of the first season of the excavation at Tomb-e Pargan (carried out in April 2012) confirmed the initial dating of the site to the Sasanian period, and have revealed an interesting circular structure from Late Sasanian times. Apart from the coins, fragments of stone vessels and a few glass and metal objects, pottery is the most important find. Since the discovered coins have fairly securely dated the mound of Tomb-e Pargan, it can therefore serve as a chronological point of reference for other Late Sasanian ceramics found in the northern areas of the Persian Gulf basin.